The GPRC6A receptor displays constitutive internalization and sorting to the slow recycling pathway - Jacobsen, Stine Engesgaard (J Biol Chem, 2017)
The class C G protein-coupled receptor GPRC6A is a putative nutrient-sensing receptor and represents a possible new drug target in metabolic disorders. However, the specific physiological role of this receptor has yet to be identified, and the mechanisms regulating its activity and cell surface availability also remain enigmatic. In the present study, we investigated the trafficking properties of GPRC6A by use of both a classical antibody feeding internalization assay in which cells were visualized using confocal microscopy and a novel internalization assay that is based on real-time measurements of fluorescence resonance energy transfer. Both assays revealed that GPRC6A predominantly undergoes constitutive internalization, whereas the agonist-induced effects were imperceptible. Moreover, postendocytic sorting was investigated by assessing the co-localization of internalized GPRC6A with selected Rab protein markers. Internalized GPRC6A was mainly co-localized with the early endosome marker Rab5 and the long loop recycling endosome marker Rab11 and to a much lesser extent with the late endosome marker Rab7. This suggests that upon agonist-independent internalization, GPRC6A is recycled via the Rab11-positive slow recycling pathway, which may be responsible for ensuring a persistent pool of GPRC6A receptors at the cell surface despite chronic agonist exposure. Distinct trafficking pathways have been reported for several of the class C receptors, and our results thus substantiate that non-canonical trafficking mechanisms are a common feature for the nutrient-sensing class C family that ensure functional receptors in the cell membrane despite prolonged agonist exposure.